Strategi Coping Stress Pada Remaja Dengan Orangtua Bercerai Yang Melakukan Percobaan Bunuh Diri - Ummaya, Zaski; Oktaviana, Rina (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2026)
This study aims to analyze the stress coping strategies of two Indonesian female adolescents (MA and NA, aged 20) from divorced families and with a history of repeated suicide attempts. The study used a qualitative approach with an intrinsic case study design. Data were collected through in-depth interviews, participant observation, and document analysis to understand the psychological dynamics and coping mechanisms used by the subjects in dealing with emotional stress. The results showed that both participants experienced complex trauma since their parents' divorce in childhood, which was exacerbated by dysfunctional family conditions such as domestic violence, infidelity, parental discrimination, and minimal social support. Initially, both subjects used maladaptive, emotion-based coping strategies such as escape-avoidance, social isolation, and self-harm. Over time, their coping patterns developed differently: MA shifted to religious coping through worship activities and spiritual reflection, which increased resilience and self-acceptance, while NA relied more on limited social support and conflict avoidance, but still showed emotional vulnerability. The contribution of this study lies in enriching the study of the coping dynamics of divorced adolescents with a history of suicide attempts in the Indonesian socio-cultural context. Practically, these findings imply the importance of comprehensive psychological interventions through coping skills training, family counseling. Keywords: coping strategies, suicide attempts, adolescents, parental divorce, qualitative case study, religious coping, dysfunctional family